Services-oriented URL filtering and verification. (1st January 2013) - Wang, Aili; Wang, Chao; Li, Xi; Zhou, Xuehai; Nedjah, Nadia
Teenagers' online safety problem has become increasingly important. To tackle this problem, this paper proposes a services-oriented URL filtering and verification mechanism. A services-oriented browser architecture prototype has been implemented, named SOBA. SOBA is the first in literature that introduces SOA concepts into the web browser design paradigm. It contains a server cluster, which employs URL filter functions to verify the URL access, while whitelists and validation results are wrapped as services. Meanwhile, a customised SOBA client is in charge of data conversion and website navigation while verification workloads are deployed on the server side. Administrators can manage URL databases through back stage websites. A prototyping software browser of SOBA demonstrates that SOA concepts can greatly improve the online safety with high flexibility and modularity.